A Policy and Practice Review of English Education in Chinese Primary and Secondary Schools - Tang, Jun (Pacific International Journal, 2025)
This study offers a comprehensive review of English education policies and classroom practices in China’s primary and secondary schools, focusing on developments from 2001 to 2022. It examines the evolution of national curriculum reforms emphasizing communicative competence, intercultural awareness, and competency-based education, particularly the 2022 Curriculum Standards. Despite significant policy progress, persistent regional disparities in teacher qualifications, training, resources, and assessment practices continue to hinder equitable implementation. Case comparisons between urban and rural schools illustrate the challenges of translating policy into practice, revealing gaps in pedagogical approaches and infrastructural support. The study highlights systemic constraints such as the dominance of exam-oriented assessments and uneven digital resource distribution that limit the realization of curriculum goals. Recommendations include targeted teacher development, assessment reform, infrastructure investment, and enhanced policy-practice integration to improve the quality and equity of English education in China. This analysis contributes to a deeper understanding of the complexities in reforming large-scale education systems and provides insights for policymakers and educators aiming to foster effective English language learning in diverse contexts.